BIMBINGAN DALAM MENUMBUHKAN SIFAT MALU PERSPEKTIF HADIS NABI SAW - Sukmasari Dewi Chan; Al Halik (Jurnal Bimbingan Penyuluhan Islam, 2020)
Abstract Don't get embarrassed, this is what the author will cover in this article. The author departs from the phenomenon of waning shame that is rife today. A person can easily indulge in his genitals, indulge in disgrace, or walk in front of the camera which is then shown to the crowd. Unfortunately there are still many who feel ashamed to do good, convey the truth, study and others. Therefore in this article the writer will explain how the hadith of the Prophet SAW views shame itself. The author uses the maudhu'iy method, collecting traditions that have a theme related to the title the author adopts. To trace the hadiths related to the shyness of the author, use the Kitab al-Mu'jam al-Mufahras li Alfazh al-Hadis al-Nabawi by A.J Weinsink with the keyword that the author searched for was.